2019
DOI: 10.1002/htj.21504
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study on thermal management of concentrated photovoltaic cell using loop heat pipe and heat sink

Abstract: One of the most critical innovations in the solar energy conversion is the use of concentrators for generating power from a smaller area of the cell. The thermal management has an exceptional role in the concentrated photovoltaic (CPV) cell, without which the operating temperature will increase owing to the thermal degradation. In the present study, a prototype of low CPV with single‐cell configuration using a Fresnel lens and a manual tracker with geometrical concentration ratio of up to 25 Suns is made. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Ref. [38] stated heat pipe heat sink dissipates flux in CPV. Researchers reported that under 25 suns, the heat pipe and heat sink could cool CPV to 37.8 • C and 54.16 • C, respectively.…”
Section: Types and Classification Of Cooling Techniques In Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [38] stated heat pipe heat sink dissipates flux in CPV. Researchers reported that under 25 suns, the heat pipe and heat sink could cool CPV to 37.8 • C and 54.16 • C, respectively.…”
Section: Types and Classification Of Cooling Techniques In Solar Cellsmentioning
confidence: 99%
“…It collects the heat from the PV and dissipates it utilising a convector or heat sink. Several researchers have highlighted that active cooling is more efficient and suitable for high concentrations [19,38,42,43]. However, one of the limitations posed by AC includes temperature non-uniformity.…”
Section: Types and Classification Of Cooling Techniques In Solar Cellsmentioning
confidence: 99%
“…There are two major cooling techniques of the CPV systems; the first one is the passive cooling, using heat sink, heat pipe, free air and phase change materials, while the active cooling uses flowing fluids (such as water or air) through channels, jet impingement, and mini channel and microchannel cooling methods [7][8][9]. It is worthiest to apply the passive cooling mechanism to dissipate heat and cool the solar cells under a CR less than 10×, as, depending usually on the weather conditions [10][11][12], increasing the convective heat transfer area can easily increase the dissipated heat rate and the solar cell efficiency. On the other hand, for High Concentration Ratios (100× ≤ CR ≤ 1000×) or Ultra-High Concentration Ratios (CR ≥ 1000×), using the active cooling techniques is more efficient to maintain CPV system temperature approximately constant over a long period under a wide range of Concentration Ratios (CR)s. Active cooling has better performance especially under harsh environmental conditions like that of Saudi Arabia [4,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Cell temperature increases if the waste heat is not removed, therefore the cell voltage/power decreases with an increase in cell temperature. 1,2 The conversion of solar energy into electricity by PV cells has been performed at various efficiency levels ranging from 7% to 40%. The efficiency of PV modules decreases with heating, and PV cells will also experience long-term failure if the temperature reaches a certain limit, so this issue has been addressed and resolved.…”
Section: Introductionmentioning
confidence: 99%